Soil fertility and drought interact to determine large variations in wood production for a hyperdominant Amazonian tree species - Durgante, Flavia Machado; Higuchi, Niro; Ohashi, Shinta; Householder, John Ethan; Lima, Adriano José Nogueira; Ishizuka, Moriyoshi; Wittmann, Florian; dos Santos, Joaquim; Carneiro, Vilany Matilla Colares; Xu, Xiaomei; do Nascimento, Claudete Catanhede; Schöngart, Jochen; et al. (Frontiers in Forests and Global Change, 2023)
The productivity of the Amazon Rainforest is related to climate and soil fertility. However, the degrees to which these interactions influence multiannual to decadal variations in tree diameter growth are still poorly explored. To fill this gap, we used radiocarbon measurements to evaluate the variation in tree growth rates over the past decades in an important hyperdominant species, Eschweilera coriacea (Lecythidaceae), from six sites in the Brazilian Amazon that span a range of soil properties and climate. Using linear mixed-effects models, we show that temporal variations in mean annual diameter increment evaluated over a specific time period reflect interactions between soil fertility and the drought index (SPEI - Standardized Precipitation and Evapotranspiration Index). Our results indicate that the growth response of trees to drought is strongly dependent on soil conditions, a facet of forest productivity that is still underexplored, and which has great potential for improving predictions of future tropical tree growth in the face of projected climate change.